The Influence of Digitalization Technology and Social Use on Human Resource Development in The Tourism Sector - Aulia Rayhana Mohammad; Sabran; Achmad Zais (Global Research Collaboration, 2026)
Digital transformation has emerged as a critical factor in enhancing the competitiveness of regional tourism, including in Kutai Barat Regency. This study aims to examine the influence of digitalization and social media on the development of human resources (HR) in local tourism. Physical data indicate that the adoption of digital platforms by tourism actors has contributed to an approximate 30% increase in tourist visits over the past two years, particularly through nature- and culture-based destination promotion on social media. This research employs a qualitative approach, using in-depth interviews with tourism business operators, destination managers, and local communities. The analysis reveals that digitalization serves as a strategic tool to improve technical competencies, digital communication skills, and marketing networks for micro, small, and medium enterprises (MSMEs) and tourism practitioners. Social media also functions as a knowledge-sharing space, fostering collaboration and informal learning ecosystems that strengthen HR professionalism. Nevertheless, challenges such as limited infrastructure, unequal internet access, and digital literacy gaps continue to constrain the full potential of digital transformation. The study concludes that digitalization and social media significantly enhance the capacity and quality of tourism HR in Kutai Barat. Local government interventions, including digital literacy programs, MSME mentoring, and youth empowerment as innovation agents, are essential to support sustainable tourism development. These findings underscore the importance of integrating technology-driven strategies with community-based capacity building to achieve resilient and competitive local tourism sectors.